B-cell treatment in ANCA-associated vasculitis. (29th April 2020) - Karras, Alexandre; Lazareth, Hélène; Chauvet, Sophie
Abstract: The pivotal role of B-cells in ANCA-associated vasculitis has been suggested by experimental data that demonstrate the direct pathogenicity of ANCAs. Rituximab (RTX), an anti-CD20 monoclonal antibody that targets B-cells, has proven its efficacy for induction of remission in severe ANCA vasculitis. RTX is equivalent to CYC for induction of remission, and is probably superior in relapsing patients. Long-term B cell depletion by prolonged RTX treatment has been shown to significantly reduce the relapse rate, when compared with AZA maintenance therapy. Biomarkers, such as B-cell subpopulations or ANCA monitoring, may help the clinician to determine the optimal dose and duration of RTX therapy.